Identification of the Binding Sites on Rab5 and p110beta Phosphatidylinositol 3-kinase. Issue 1 (December 2017) - Whitecross, Dielle; Anderson, Deborah
Abstract Rab5 is a small monomeric GTPase that mediates protein trafficking during endocytosis. Inactivation of Rab5 by GTP hydrolysis causes a conformational change that masks binding sites on its "switch regions" from downstream effectors. The p85 subunit of phosphatidylinositol 3-kinase (PI3K) is a GTPase activating protein (GAP) towards Rab5. Whereas p85 can bind with both Rab5-GTP and Rab5-GDP, the PI3K catalytic subunit p110β binds only Rab5-GTP, suggesting it interacts with the switch regions. Thus, the GAP functions of the catalytic arginine finger (from p85) and switch region stabilization (from p110β) may be provided by both proteins, acting together. To identify the Rab5 residues involved in binding p110β, residues in the Rab5 switch regions were mutated. A stabilized recombinant p110 protein, where the p85-iSH2 domain was fused to p110 (alpha or beta) was used in binding experiments. Eleven Rab5 mutants, including E80R and H83E, showed reduced p110β binding. The Rab5 binding site on p110β was also resolved through mutation of p110β in its Ras binding domain, and includes residues I234, E238 and Y244. This is a second region within p110β important for Rab5 binding. The Rab5-GTP:p110β interaction may be further elucidated through the characterization of these non-binding mutants in cells.